How to Provide Functional Grammar with Typological-Diachronic Adequacy - Martín Arista, Javier (Miscelánea: A Journal of English and American Studies, 1992)
The purpose of this paper is to discuss how the theory of Functional Grammar as stated by Dik (1979 and 1989) can be provided with Typological-Diachronic Adequacy. The reason why this new concept is coined is that, in spite of the fact that one of the main concerns of Functional Grammar is how to achieve typological adequacy (more than eighty languages —most of which are not Indo-uropean— have been successfully discussed from the point of view of FG), this theoretical framework still lacks a detailed discussion of the relationship between Diachrony and Typology.This paper revises critically the standards of adequacy proposed byTransformational Grammar and compares them with the ones put forward in the realm of Functional Grammar. In doing so, we concentrate on the specifications forDescriptive Adequacy and pay special attention to these specifications in FG. Then, after revising the constraints imposed on the power of FG , we define and explain the new concept which is proposed here: TypologicalDiachronic Adequacy. Afterwards, we go on to discuss how to provide Dik's Functional Grammar with Typological-Diachronic Adequacy and, finally, we answer the question whether or not new |constraints upon the descriptive power of the theory arise.